Biallelic COLGALT1 variants are associated with cerebral small vessel disease. Issue 6 (30th November 2018) - Miyatake, Satoko; Schneeberger, Sacha; Koyama, Norihisa; Yokochi, Kenji; Ohmura, Kayo; Shiina, Masaaki; Mori, Harushi; Koshimizu, Eriko; Imagawa, Eri; Uchiyama, Yuri; Mitsuhashi, Satomi; Frith, Martin C.; et al.
Abstract : Objective: Approximately 5% of cerebral small vessel diseases are hereditary, which include COL4A1/COL4A2 ‐related disorders. COL4A1/COL4A2 encode type IV collagen α1/2 chains in the basement membranes of cerebral vessels. COL4A1/COL4A2 mutations impair the secretion of collagen to the extracellular matrix, thereby resulting in vessel fragility. The diagnostic yield for COL4A1/COL4A2 variants is around 20 to 30%, suggesting other mutated genes might be associated with this disease. This study aimed to identify novel genes that cause COL4A1/COL4A2 ‐related disorders. Methods: Whole exome sequencing was performed in 2 families with suspected COL4A1/COL4A2 ‐related disorders. We validated the role of COLGALT1 variants by constructing a 3‐dimensional structural model, evaluating collagen β (1‐O) galactosyltransferase 1 (ColGalT1) protein expression and ColGalT activity by Western blotting and collagen galactosyltransferase assays, and performing in vitro RNA interference and rescue experiments. Results: Exome sequencing demonstrated biallelic variants in COLGALT1 encoding ColGalT1, which was involved in the post‐translational modification of type IV collagen in 2 unrelated patients: c.452 T > G (p.Leu151Arg) and c.1096delG (p.Glu366Argfs*15) in Patient 1, and c.460G > C (p.Ala154Pro) and c.1129G > C (p.Gly377Arg) in Patient 2. Three‐dimensional model analysis suggested that p.Leu151Arg and p.Ala154Pro destabilized protein folding, which impaired enzymatic activity. ColGalT1 protein expression and ColGalT activity in Patient 1 were undetectable. RNA interference studies demonstrated that reduced ColGalT1 altered COL4A1 secretion, and rescue experiments showed that mutant COLGALT1 insufficiently restored COL4A1 production in cells compared with wild type. Interpretation: Biallelic COLGALT1 variants cause cerebral small vessel abnormalities through a common molecular pathogenesis with COL4A1/COL4A2 ‐related disorders. Ann Neurol 2018;84:843–853